Generation of a Multi-Locus Chicken Introgression Line to Study the Effects of Genetic Interactions on Metabolic Phenotypes in Chickens - Ek, Weronica; Marklund, Stefan; Ragavendran, Ashok; Siegel, Paul B.; Muir, William; Carlborg, Örjan (Frontiers in Genetics, 2012)
Most biological traits are regulated by a complex interplay between genetic and environmental factors. By intercrossing divergent lines, it is possible to identify individual and interacting QTL involved in the genetic architecture of these traits. When the loci have been mapped, alternative strategies are needed for fine-mapping and studying the individual and interactive effects of the QTL in detail. We have previously identified, replicated and fine-mapped a four-locus QTL network that determines nearly half of the eight-fold difference in body-weight at 56 days of age between two divergently selected chicken lines. Here, we describe, to our knowledge, the first generation of a three-locus QTL introgression line in chickens to further study the effect of three of the interacting loci in this network on metabolic phenotypes. Recurrent marker assisted backcrossing was used to simultaneously transfer QTL alleles from the low-weight selected line into the high-weight selected line. Three generations of backcrossing and one generation of intercrossing resulted in an introgression line where all three introgressed QTL and several unlinked and linked control-loci were segregating at nearly expected allele frequencies. We show that marker-based sexing is an efficient method for sexing breeding populations and how intensive selection can be applied using artificial insemination to generate large half-sib families. Based on our empirical observations, we provide recommendations for future introgression-line breeding experiments. In the future, use of this confirmed introgression line will facilitate detailed studies of the effects of genetic interactions on complex traits.